2018
DOI: 10.3390/ijms19123859
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Biocompatible Platform: Lipid-Based and Bio-Inspired Smart Drug Delivery Systems for Cancer Therapy

Abstract: Designing new drug delivery systems (DDSs) for safer cancer therapy during pre-clinical and clinical applications still constitutes a considerable challenge, despite advances made in related fields. Lipid-based drug delivery systems (LBDDSs) have emerged as biocompatible candidates that overcome many biological obstacles. In particular, a combination of the merits of lipid carriers and functional polymers has maximized drug delivery efficiency. Functionalization of LBDDSs enables the accumulation of anti-cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 152 publications
(150 reference statements)
0
26
0
Order By: Relevance
“…Light-responsive biological (bioinspired) drug carriers can be considered as one of the most attractive delivery systems, replicating features that are similar to the biological objects [212]. The main advantages of bioinspired carriers are their ability to interact with specific sites of the body, their cell/tissue entering mechanisms, capability to avoid the immune responses, and prolonged circulation times in biological fluids [212,213]. Light-responsive bioinspired carriers include the use of (4.…”
Section: Composite Light-sensitive Bioinspired Delivery Platformsmentioning
confidence: 99%
“…Light-responsive biological (bioinspired) drug carriers can be considered as one of the most attractive delivery systems, replicating features that are similar to the biological objects [212]. The main advantages of bioinspired carriers are their ability to interact with specific sites of the body, their cell/tissue entering mechanisms, capability to avoid the immune responses, and prolonged circulation times in biological fluids [212,213]. Light-responsive bioinspired carriers include the use of (4.…”
Section: Composite Light-sensitive Bioinspired Delivery Platformsmentioning
confidence: 99%
“…According to Kurien et al (2007), the solubility of curcumin in water could be maximized by dissolving first in methanol and then diluting with water or even using heat. Furthermore, the use of the cell membrane can improve the bioavailability of curcumin using lipid-based nanoparticles that capture hydrophobic drugs, and also allow intravenous injection (Kim et al, 2018). We also showed that curcumin has additional therapeutic benefits by using R/P-cGNS for cancer therapies including photothermal effects, controlled drug release at elevated temperature, and the targeting of cancer cells through PLTs.…”
Section: Discussionmentioning
confidence: 77%
“…Therefore, the specific emphasis should be given to the toxicity of the blank nanoparticles (non-drug loaded particles) 44. Generally, lipid nanoparticles are considered biocompatible,46 and our in-vitro cytotoxicity study of blank NLC demonstrated that no significant toxicity. However, since there are a variety of cells affected by nanoparticle exposure in the different route of administration, cytotoxicity assays using single-cell studies is not sufficient 47.…”
Section: Discussionmentioning
confidence: 91%